2010
DOI: 10.4028/www.scientific.net/amr.168-170.541
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cement Water Reducer of Modified Lignosulfonate

Abstract: In this paper, the cement water reduction agent from modified lignosulfonate was synthesizd using a new process consisting of pre-oxidation, hydroxymethylation and sulfonation. The optimum synthesis conditions were identified: the oxidizing agent dosage is 15%, reaction temperature is 80-90oC, the dosage of formaldehyde is 30%, reaction temperature is about 95oC, pH is about 9.5. Fluidity of cement paste can be measured under the conditions of the addition of 0.25%, and the water-cement ratio is 0.4%. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…It was verified that the fluidity of the cement paste was positively correlated with the water reducing rate, and the water reducing rate could be quickly evaluated by testing the fluidity of the cement paste. , Hence, in this work, cement paste fluidity was used to evaluate the water reducing performance of the lignin products. The fluidity of the cement paste was determined according to the Chinese National Standard of GB/T8007-2012 .…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…It was verified that the fluidity of the cement paste was positively correlated with the water reducing rate, and the water reducing rate could be quickly evaluated by testing the fluidity of the cement paste. , Hence, in this work, cement paste fluidity was used to evaluate the water reducing performance of the lignin products. The fluidity of the cement paste was determined according to the Chinese National Standard of GB/T8007-2012 .…”
Section: Methodsmentioning
confidence: 89%
“…Wu studied a new modification process by preoxidation, hydroxymethylation, and sulfonation to modify lignosulfonate, which was derived from eucalyptus kraft pulping black liquor. The results showed that the fluidity of cement paste could reach 178 mm that was close to the performance of high efficient water reducer . Yu studied the modification of sodium lignosulfonate (SLS) via combining oxidation–sulfomethylation.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fact that the fluidity of the cement paste was not significantly enhanced when using LS modified via laccase-oxidative polymerization (with increased M w of 3,6800 Da [ 27 ] but mostly unaltered zeta potential) suggests that the number of ionizable groups did not change much, as proposed by Areskogh and co-workers [ 27 ]. Indeed, the increase of the number of sulphonic groups is required to chelate calcium ions hence, modifying the adsorption of LS on the surface of cement particles, by altering the electrostatic repulsion and improving fluidity [ 24 , 76 , 77 ]. Therefore, this outcome suggests that the sole increase of molecular weight of LS is not crucial or even relevant to enhance the dispersing properties of LS.…”
Section: Resultsmentioning
confidence: 99%
“…Since 1935, great progress has been made by chemical modification to improve the application performances of CL, such as water-reducing ratio, air-entraining property and hydration-delaying capacity [1][2][3][4][5][6]. While there are still some problems remaining to be settled in practical applications, especially the influence of CL on the setting of cement.…”
Section: Introductionmentioning
confidence: 99%